MUS81 Participates in the Progression of Serous Ovarian Cancer Associated With Dysfunctional DNA Repair System - Lu, Renquan; Xie, Suhong; Wang, Yanchun; Zheng, Hui; Zhang, Hongqin; Deng, Minjie; Shi, Weizhong; Zhong, Ailing; Chen, Miaomiao; Zhang, Meiqin; Xu, Xiaofeng; Shammas, Masood A.; et al. (Frontiers in Oncology, 2019)
Objective: Methyl methanesulfonate ultraviolet sensitive gene clone 81 (MUS81) is a structure-specific endonuclease that plays an important role in DNA repair system of cancer cells. In this study, we aim to investigate potential association between the dysfunction of MUS81 and the progression of Serous Ovarian Cancer (SOC). Methods: To investgate the association between MUS81 and prognosis of SOC, immunohistochemistry and qPCR were used to analyse the level of MUS81 expression, and transcriptional profile analysis and protein interaction screening chip was used to explore the MUS81 related signal pathways. Random amplified polymorphic DNA (RAPD) analysis, immunofluorescence and comet assays were performed to evaluate genomic instability and DNA damage status of transduced SOC cells. Experiments both in vitro and in vivo were conducted to verify the impact of MUS81 silencing on chemotherapeutic drug sensitivity to SOC. Results: The overexpression of MUS81 in SOC tissues was related to poor clinical outcomes. The data of transcriptional chip showed that MUS81 was involved in multiple pathways associated with DNA repair. Deficiency of MUS81 intensified the genome instability of SOC cells, and promoted the emergence of DSBs and restrained the formation of RAD51 foci in SOC cells with exposure to UV. Furthermore, downregulation of MUS81 enhanced the sensitivity to Camptothecin and Olaparib in SOC cell lines and xenograft model. Conclusions: MUS81 is involved in the progression of SOC and plays an important role of the susceptibility to chemotherapeutic agents. MUS81 might represent a novel molecular target for SOC chemotherapy.